Evaluation of bone regeneration using human derived-gingival mesenchymal stem cells loaded on beta tricalcium phosphate and hyaluronic acid: an experimental study - Abo-Zaid, Mohammed Abd-ElFattah; El Razzak, Mona Y. A.; Sarhan, Naglaa I.; Alkaleny, Heba H.; Badr, Ahamed M. (Tanta Dental Journal, 2024)
Background Healing of critical-sized bone defects (CSDs) is a challenging problem in both clinical and research settings. Aim The present study aimed to assess the regenerative capacity of human gingival-derived mesenchymal stem cells (hGMSCs) loaded on beta-tricalcium phosphate scaffold (β-TCP) and hyaluronic acid (HA) gel in surgically created standardized CSDs in rabbit's femurs. Materials and methods To achieve this aim, CSDs of 6 mm diameter each, were unilaterally created in femur of adult New Zeeland male white rabbits (n = 18). The rabbits were then divided randomly into three groups and received the following treatment modalities: group A (study group): six defects were treated with hGMSCs loaded on β-TCP scaffold combined with HA gel; group B (positive control group): six defects (n = 6 rabbits) were treated with β-TCP combined with HA gel; group C (negative control group): three defects were left without intervention. Two rabbits from groups A, B and one rabbit from group C were sacrificed at 6 weeks, femurs were dissected out to evaluate bone healing histologically and histomorphometrically. Results The findings of this study indicate that, hGMSCs exhibited fibroblast like morphology and expressed phenotypic MSCs markers (positive for cluster of differentiation CD105 and negative for CD34). Histologically, local application of hGMSCs loaded on β-TCP scaffold with HA gel showed enhanced pattern of bone regeneration as compared to the unloaded scaffold. Histomorphometrically, there was a statistically significant difference in the newly formed bone between the bony defects treated with hGMSCs and control groups. Conclusion GMSCs can be considered as a dependent source of MSCs with bone tissue regenerative capacity.